2021
DOI: 10.1177/15330338211019433
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of KDR Genetic Variation on the Efficacy and Safety of Patients With Advanced NSCLC Receiving First-Line Bevacizumab Plus Chemotherapy Regimen

Abstract: Objective: Angiogenesis plays an important role in the growth and metastasis of non-small cell lung cancer (NSCLC). Bevacizumab is a humanized monoclonal antibody that mainly acts on vascular endothelial growth factor A (VEGFA). Kinase insert domain receptor (KDR) is the most important target of VEGFA. The aim of present study was to investigate the influence of KDR genetic variation on the efficacy and safety of patients with advanced NSCLC receiving first-line bevacizumab plus chemotherapy regimen. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…To our knowledge, ECOG performance status was confirmed to be an independent prognostic factor to predict the survival among patients with NSCLC. 29 Furthermore, Cox regression analysis in our study also suggested that patients with ECOG performance status 2 score were correlated with worse PFS independently. Another two retrospective studies regarding anlotinib monotherapy for patients with previously treated NSCLC were reported recently.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, ECOG performance status was confirmed to be an independent prognostic factor to predict the survival among patients with NSCLC. 29 Furthermore, Cox regression analysis in our study also suggested that patients with ECOG performance status 2 score were correlated with worse PFS independently. Another two retrospective studies regarding anlotinib monotherapy for patients with previously treated NSCLC were reported recently.…”
Section: Discussionsupporting
confidence: 68%
“…And the specific usage and dosage of chemotherapy and bevacizumab was similar with the previous study. 20…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of RNA extraction and mRNA expression experiment was performed according to the previous study. 20 Forward primer of GSTP1 gene was 5’-GTAGTTTGCCCAAGGTCAAG-3,’ the reverse primer was 5’-AGCCACCTGAGGGGTAAG-3.’ In addition, GSTP1 mRNA expression status was divided into GSTP1 high expression (GSTP1H) and GSTP1 low expression (GSTP1L) according to the median GSTP1 mRNA relative expression to identify the potential association with OS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations